THE ADDITION OF PETROLEUM BENZIN IN MIXING OF CRUDE PALM OIL AND METHANOL ON BIODIESEL PRODUCTION - Abdullah Abdullah; F Fadhillah; Supranto Supranto; A. Prasetya (Indonesian Journal of Chemistry, 2010)
Research on transesterification of crude palm oil (CPO) using petroleum benzin as solvent has been done. This research aims to determine the optimum concentration of catalyst KOH and NaOH, mole ratio of methanol to oil, volume ratio of solvent to oil, and temperature range of solvent. This research also observes the influence of changing in methanol concentration and levels of palm oil free fatty acids (FFA) on biodiesel production. In this research, transesterification was preceded by esterification for 10 min using sulphuric acid catalyst. The results showed that KOH gave better results than NaOH as catalyst with optimum concentration was 1.75% (w/v). Mole ratio of methanol to palm oil optimum was 6:1, and volume ratio of solvent to palm oil optimum was 2:5. Optimum temperature range of the solvent was 70-90 °C. Decreasing on concentration of methanol, and increasing of free fatty acids (FFA) level gave negative impact on the biodiesel production, more over on transesterification without solvent. The characteristics (phosphor content, density, water content, ash content, carbon residue, energy content and chemical components) of biodiesel which was produced using petroleum benzin relatively similar to biodiesel produced in the normal way (without solvent). Decreasing on concentration of methanol, and increasing on level of free fatty acids (FFA) gave a negative impact on the biodiesel, more over on transesterification without solvent.